Analisis Keputusan Mahasiswa dalam Menggunakan Vape melalui Pengetahuan Produk, Group Reference dan Harga - Arsana, I Made Mangku; Yuliana, Ika; Wardi, Putri Amalia; Jati, L. Jatmiko; Nirwana, Baiq Nadia (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
Electronic cigarettes (vapes) have transformed the consumption habits of millennials, shifting from traditional smokes to a contemporary alternative. University students, who are the primary consumers of conventional cigarettes and vapes, evaluate multiple factors while choosing a vape product. Factors impacting students' use of vapes include product knowledge, peer influence, and cost.  This research utilises a descriptive quantitative methodology by administering questionnaires to 100 university students in Mataram City. The gathered data is subsequently analysed utilising SPSS version 21. The findings demonstrate that Product Knowledge and Group Reference exert a positive and significant impact on students' decisions to utilise vapes. Simultaneously, price exerts a negligible and inconsequential influence on students' choices to utilise vapes.